Numbers, distribution and breeding success of Whooper Swans Cygnus cygnus and Mute Swans C. olor in central Kazakhstan, USSR, in 1985 and 1987 - Vinogradov, V G; Auezov, E M (Wildfowl, 2013)
No abstract.